Home » Blog » Determine functions u and v satisfying given differential equations

Determine functions u and v satisfying given differential equations

The graph of a solution u of the differential equation

    \[ y'' - 4y' + 29y = 0 \]

intersects the graph of a solution v of the differential equation

    \[ y'' + 4y' + 13y = 0 \]

at the origin. Furthermore, the two curves have equal slopes at the origin. Determine formulas for the functions u and v if

    \[ u'\left( \frac{1}{2} \pi \right) = 1. \]


First, we compute the general solutions of the second-order differential equation

    \[ y'' - 4y' + 29y = 0. \]

This is an equation of the form

    \[ y'' + ay' + by = 0 \qquad \text{with} \qquad a = -4, \ \ b = 29. \]

From this we compute d = a^2 - 4b = -100, so d < 0 and k = \frac{1}{2} \sqrt{-d} = 5. Using Theorem 8.7 (pages 326-327 of Apostol) we have

    \[ y = e^{2x} (c_1 \cos (5x) + c_2 \sin (5x)). \]

Next, we compute the general solutions of the second-order differential equation

    \[ y'' + 4y' + 13y = 0. \]

This is again an equation of the form

    \[ y'' + ay' + by = 0 \qquad \text{with} \qquad a = 4, \ \ b = 13. \]

From this we compute d = a^2 -4b = -36 so d < 0 and k = \frac{1}{2} \sqrt{-d} = 3. Again, applying Theorem 8.7 (pages 326-327 of Apostol) we have

    \[ y = e^{-2x} (c_1 \cos (3x) + c_2 \sin (3x)). \]

Now, let

    \[ u = e^{2x}(a_1 \cos (5x) + a_2 \sin (5x)), \qquad v = e^{-2x} (b_1 \cos (3x) + b_2 \sin (3x)). \]

We know that the solutions we want intersect at the origin, hence we must have u(0) = v(0) = 0. So,

    \begin{align*}  u(0) &= 0 &\implies && a_1 &= 0, \\  v(0) &= 0 & \implies && b_1 &= 0. \end{align*}

Plugging these values for the constants a_1 and b_1 into our expressions for u and v we compute the first derivatives,

    \begin{align*}  u' &= a_2 (2e^{2x} \sin (5x) + 5e^{2x} \cos (5x)) \\  v' &= b_2 (-2e^{-2x} \sin (3x) + 3e^{-2x} \cos (3x)). \end{align*}

Next, we are given that the particular solutions u and v we want have equal slopes at the origin. This means u'(0) = v'(0). Hence,

    \[ u'(0) = v'(0) \quad \implies \quad 5a_2 = 3b_2 \quad \implies \quad b_2 = \frac{5}{3} a_2. \]

Finally,

    \[ u' \left( \frac{\pi}{2} \right) = 1 \quad \implies \quad 2a_2 e^{\pi} = 1 \quad \implies \quad a_2 = (2e^{pi})^{-1} \quad \implies \quad b_2 = \frac{5}{6e^{\pi}}. \]

Thus,

    \[ u(x) = \frac{1}{2} e^{2x-\pi} (\sin 5x), \qquad v(x) = \frac{5}{6} e^{-2x-\pi} (\sin 3x). \]

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):